Strengthening and Development of Social and Economic Potential to Improve Welfare of the Tibelat Art Studio Community - Seva, Kristining; Demetrius, Wilfridus; Zhukhruffa, Syayu (TEMALI : Jurnal Pembangunan Sosial, 2024)
Strengthening and developing social and economic potential is very important to improve community welfare. This can be achieved through a variety of strategies, including improving social programs, developing culture, and creating opportunities for social and economic growth. For people with low incomes, performing arts can also be used as a way of life. The income of the Reak Tibelat Art Studio, which is located in Kampung Jati, Pasir Biru Village, comes from Reak Art performances by local people who hire their services for child or relative circumcision celebrations. Apart from that, their income also comes from visits from domestic and foreign tourists who hire their performance services for certain events. The fact that has occurred so far is that the promotional media related to Reak Art performances is limited to word of mouth, which is maintained by local residents without any meaningful national publications, so tourist visits are very limited. The future potential of this business remains great due to its deep-rooted tradition and philosophical values, making it a sustainable choice for celebrating events and expressing gratitude to God. To fully realize this potential, it is essential to utilize digital media for economic growth and disseminate information about the rich culture of the Reak Tibelat Art Studio. This involves increasing partners' proficiency in effectively utilizing digital platforms, websites and social media. The main focus is to train Village and Studio managers in creating a variety of digital content—images, videos, and written materials. Additionally, our science and technology training aims to improve participants' soft and hard skills in platform management and digital marketing, thereby providing benefits to all potential partners involved.